Banking concentration and financial development in the MENA region. Issue 4 (6th July 2020) - Hamadi, Hassan; Awdeh, Ali
Abstract : Purpose: Bank consolidations in many Middle East and North Africa (MENA) countries have been proceeding at a rapid pace, leading to a decline in the number of banks and an increase in market concentration. This may raise concerns regarding the impact of such increase in concentration on the behaviour of banks and consequently on the financial development. Therefore, this study aims to examine the impact of concentration on the financial development of MENA region. Design/methodology/approach: The study adopts fully modified ordinary least squares model on a heterogeneous, non-stationary, cointegrated panel data set. The exploited panel is formed of 15 MENA countries and covers the period 1996–2014. Findings: The empirical results show that concentration per se is not harmful for financial development. Nevertheless, concentration combined with bank market power may deteriorate the development of MENA financial systems. Originality/value: In addition to considering an understudied region, the research presents very important findings, which suggest that if banks obtain market power, an increase in concentration following a wave of bank mergers, could weaken the financial development.